Seed Quality of Greengram Stored in Different Storage Environment - A.K.M.R. Amin, Mirza Hassanuzzaman, M.M. Alam, M.H. Ali, (Journal of Phytology, 2009)
A laboratory experiment was conducted with mungbean seeds kept in three different containers. Three containers were tin pot, poly bag and jute bag and stored at room temperature and RH for three months (23 June-23 September) in the Laboratory of Agronomy Department, Sher-e- Bangla Agricultural University, Dhaka, Bangladesh to study their storage behavior, germination percentage and quality. The seed of jute bag came to the contact with air and their moisture contents was decreased from initial moisture content and remained near to their Equilibrium Moisture content (EMC), moisture content of the seeds of jute bag was found decreased from 7.50% to 16.70% within 6 weeks of storage. But moisture contents of seeds of tin pot and poly bag remained approximate constant throughout 7 weeks period. As tin pot and poly bag was more or less air tight so the seeds of these container could not come to the contact with ambient room air, resulting no significant change of their moisture content. Germination capacity of the seeds of tin pot was found decreased from 78% to 68% and 77% to 58% in the seeds of poly bag. Germination capacity of the seeds of jute bag was found decreased from 73% to 48%t in 5th week of storage. So, the germination capacity was also found a little bit higher than the seeds of other containers. Considering three different container, tin pot container has been proved much more safe and secured than jute bag or poly bag container.